Identification of alternative splicing and negative splicing activity of a nonsegmented negative-strand RNA virus, Borna disease virus - Tomonaga, Keizo (The National Academy of Sciences, 2000)
Borna disease virus (BDV) is a nonsegmented negative-strand RNA virus that belongs to the Mononegavirales. Unlike other animal viruses of this order, BDV replicates and transcribes in the nucleus of infected cells. Previous studies have shown that BDV uses RNA splicing machinery for its mRNA expression. In the present study, we identified spliced RNAs that use an alternative 3′ splice site, SA3, in BDV-infected cell lines as well as infected animal brain cells. Transient transfection analysis of cDNA clones of BDV RNA revealed that although SA3 is a favorable splice site in mammalian cells, utilization of SA3 is negatively regulated in infected cells. This negative splicing activity of the SA3 site is regulated by a putative cis-acting region, the exon splicing suppressor (ESS), within the polymerase exon of BDV. The BDV ESS contains similar motifs to other known ESSs present in viral and cellular genes. Furthermore, our results indicated that a functional polyadenylation signal just upstream of the BDV ESS is also involved in the regulation of alternative splicing of BDV. These observations represent the first documentation of complex RNA splicing in animal RNA viruses and also provide new insight into the mechanism of regulation of alternative splicing in animal viruses.